Strengthening flood resilient development in malaysia through integration of flood risk reduction measures in local plans. (March 2021) - Norizan, Nur Zainul Arifin; Hassan, Norhaslina; Yusoff, Mariney Mohd
Highlights: Within disaster management discourse, development planning has significant roles to reduce disaster risk in creating resilient development. In Malaysia, the notion of disaster resilience has become a recent development agenda in response to disaster risks especially flooding. Statutory development plan guides planning control decisions which is essential to tackle disaster-related issues in development. Preparedness and adaptation measures are essential in gearing resilience development and therefore need to be further ingrained in development planning mechanism. Abstract: The increasing flood hazards due to climate change and development pressures have called for the integration of disaster resilient attributes through holistic flood risk reduction measures in development plans. Strengthening flood resilience in development planning therefore is not only to prevent risk, but also to reduce vulnerability as well as inculcate preparedness to adapt and better respond to disaster. In Malaysia, the notion of disaster resilience has become a recent development agenda in response to disaster risks especially flooding since the country is highly prone to such hazard. Flood reduction measures have become the key elements in Malaysia's development plans at all levels, but little is known about the range of such measures being integrated in local development plan, which is a statutory development plan that guides planning control decisions and enable local communities to participate in local development agenda. Therefore, this study seeks to analyse the extent to which flood risk reduction measures are being integrated into local plans in Malaysia towards flood resiliency. The study, however, is limited to qualitative approach based on literature and content analysis of selected local plans. The finding suggests that all studied plans have integrated most measures to avoid risk and reduce vulnerability although measures on disaster preparedness were inadequate. There is a need thus, to further strengthen disaster resilience measures in the local development plans to ingrain preparedness and adaptation with more inclusive participatory civil societies and stakeholders.